Conceptual understanding and visual representation: are they still ordinary or extraordinary issues? - Gumilar, Surya (Insitut Pendidikan Indonesia, 2023)
This article critically examines the prevalent focus on conceptual understanding in Indonesian physics education research, particularly emphasizing abstract concepts like electricity and heat transfer at different educational levels. The author challenges the common perception that certain physics concepts, such as force, are inherently abstract, asserting that all physics concepts possess an abstract nature. The recurring choice of investigating electricity-related topics, driven by their perceived abstractness, is questioned. The author observes a consistent use of similar research instruments across primary, junior high, senior high, and university levels, raising concerns about the lack of adaptation to students’ varying capabilities of abstraction. The argument is presented for aligning research topics with age-appropriate conceptual understanding, challenging the uniformity in the development of research instruments across different educational levels. In a parallel context, the article underscores the importance of visual representation as an evaluation tool in physics education. The scarcity of research in Indonesia utilizing visual representation is noted, attributed to students’ confusion and a lack of understanding. Visual representation is posited as crucial for gauging students’ comprehension of scientific concepts, with examples given in the realms of collisions and climate changes. In conclusion, the author hopes this issue becomes a reference for future physics education research, urging researchers to delve into robust studies on conceptual understanding and visual representation. The article underscores the pivotal role these elements play in shaping the trajectory of physics education research, advocating for a more nuanced and tailored approach to investigations in these areas.